2007
DOI: 10.1002/adsc.200600627
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic‐Inorganic Materials Derived from a Monosilylated Hoveyda‐type Ligand as Recyclable Diene and Enyne Metathesis Catalysts

Abstract: The synthesis of a monosilylated Hoveydatype monomer is described as well as the preparation of several organic-inorganic hybrid materials derived from it by sol-gel processes and by anchoring to commercial silica gel and MCM-41. The resulting materials were treated with first and/or second generation Grubbs catalyst to generate HoveydaGrubbs type alkylidene ruthenium complexes covalently bonded to the silica matrix. These materials are efficient recyclable catalysts for the ring-closing metathesis reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 98 publications
1
20
0
Order By: Relevance
“…As supports for immobilization both organic polymers and silica material of various types have been used [6,7]. Generally, three strategies have been developed for immobilization of Ru carbenes to the support: (i) through alkylidene ligand [8][9][10][11][12][13][14][15][16], (ii) via phosphine or N-heterocyclic carbene (NHC) ligand [17,18], and (iii) through exchange of halogen ligands [19][20][21][22][23]. As Ru-O bond dissociates and alkylidene ligand is exchanged in the initiation step [24], the propagating species of catalysts prepared in way (i) are in fact not bound to the surface of the support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As supports for immobilization both organic polymers and silica material of various types have been used [6,7]. Generally, three strategies have been developed for immobilization of Ru carbenes to the support: (i) through alkylidene ligand [8][9][10][11][12][13][14][15][16], (ii) via phosphine or N-heterocyclic carbene (NHC) ligand [17,18], and (iii) through exchange of halogen ligands [19][20][21][22][23]. As Ru-O bond dissociates and alkylidene ligand is exchanged in the initiation step [24], the propagating species of catalysts prepared in way (i) are in fact not bound to the surface of the support.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the applications of mesoporous molecular sieves as supports for immobilization of well-defined organometallic metathesis catalysts are still rare. MCM-41 was used for immobilization of 1 via PR 3 ligands [17] and via exchange of alkylidene ligands [10]. MCM-41, MCM-48 and SBA-15 were used as supports for immobilization of Mo-alkylidenes [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is also worth mentioning that the presence of metals after a metathesis reaction can promote undesired side reactions such as isomerization or degradation during workup. [37][38][39] In view of these disadvantages, several groups have synthesized heterogenized Mo- [34,35,40,41] and Ru-based [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] molecular complexes that can catalyze the olefin metathesis reaction, thereby combining the advantages of homogeneous catalysts (group tolerance, selectivity, and so on) with an easier product-catalyst separation. [34] For ruthenium carbenes, the supported catalysts have been prepared by diverse approaches that mainly differ in terms of the linking ligand and the nature of the support.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of combining the advantages of heterogeneous and homogeneous processes, many authors have synthesized well‐defined heterogeneous catalysts by supporting organometallic complexes on different solids and surfaces such as oxides or polymers 5. 9, 17, 18 In this way, some of us have recently prepared several Grubbs–Hoveyda‐type heterogenized catalysts through sol–gel procedures on suitably modified Hoveyda ligands (Scheme ) 1921. These catalysts present good activities in ring‐closing diene and enyne metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been observed that the nitro‐substituted Grubbs–Hoveyda‐based catalysts NO 2 (4) (Scheme ) require considerably lower reaction times to achieve full conversion in the first catalytic runs than the nonsubstituted catalysts H 20. 21 Nevertheless, the NO 2 (4) catalyst showed a pronounced decrease of activity upon recycling, whereas H shows similar or only slightly lower activity after several runs.…”
Section: Introductionmentioning
confidence: 99%